The Concept of Basyar in the Qur'anic Perspective: a Humanistic Psychology Approach - Sa'adah, Nailis; Soleh, Achmad Khudori (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Human, in the Qur'anic perspective, is described using various terms, one of which is Al-Basyar. The termAl-Basyar refers to the outward appearance of something beautiful and originates from the word basyarah,meaning skin. This study aims to examine and explore the concept of humans as Al-Basyar from theQur'anic perspective. This research employs a qualitative method with content analysis as the primaryapproach, focusing on the interpretation of Qur'anic verses. Primary data were derived from the Qur'an andcross-checked with secondary sources, including classical and contemporary interpretations. The findings ofstudy reveal that: (a) the word basyar appears 37 times in the Qur'an—31 times without the definitearticle (alif-lam), 5 times with the definite article, and once in the dual form; (b) there are 9 versesdescribing humans as basyar in general, highlighting their physical needs such as eating, having skin,engaging in sexual activity, and experiencing mortality; (c) 5 verses discuss the process of human creationinvolving soil, water, and the infusion of the spirit; (d) 23 verses discuss prophethood, including 13 depictingsocietal rejection and slander of prophets, and 10 emphasizing prophets as ordinary humans (basyar); (e)using a humanistic psychology perspective, basyar represents humans with basic physiological needs such aseating, drinking, sleeping, and sexual relations. This study contributes to Islamic scholarship by providingan integrative understanding of basyar as a term bridging Qur'anic theology and humanistic psychology.Furthermore, the use of content analysis as a methodological tool in exploring Qur'anic conceptsdemonstrates the potential for interdisciplinary approaches in Qur'anic studies.